The effect of impregnation of activated carbon with SnCl2.2H2O on its porosity, surface composition and CO gas adsorption - Al-Khatib, Ma’an.F; Iyuke, Sunny E; Mohamad, Abu Bakar; Daud, Wan R.W; H Kadhum, Abdul Amir; M Shariff, Azmi; Yarmo, Mohd A (Elsevier, 2002)
Activated carbon was impregnated with different concentrations of SnCl2.2H2O. Unimpregnated and impregnated activated carbons were analysed by means of physical adsorption and XPS and were tested for CO gas adsorption in a PSA system. The adsorption isotherms of N2 at 77 K were measured and showed a Type I isotherm indicating microporous carbon for all the samples. The surface area, pore volume and pore size distribution were reduced with impregnation. XPS analysis showed an increase in the intensity of Sn3d peak with impregnation. The impregnated activated carbon showed a very good adsorption ability of CO gas compared to the unimpregnated sample. The adsorptive species responsible for CO gas adsorption was confirmed to be SnO2 instead of SnO due to the former's comparative thermodynamic stability.